Influence of Novel Highly Pathogenic Avian Influenza A (H5N1) Virus Infection on Migrating Whooper Swans Fecal Microbiota - Zhao, Na; Wang, Supen; Li, Hongyi; Liu, Shelan; Li, Meng; Luo, Jing; Su, Wen; He, Hongxuan (Frontiers in Cellular and Infection Microbiology, 2018)
The migration of wild birds plays an important role in the transmission and spread of H5 highly pathogenic avian influenza (HPAI) virus, posing a severe risk to animal and human health. Substantial evidence suggests that altered gut microbial community is implicated in the infection of respiratory influenza virus. However the influence of H5N1 infection in gut microbiota of migratory birds remains unknown. In January 2015, a novel recombinant H5N1 virus emerged and killed about 100 migratory birds, mainly including whooper swans in Sanmenxia Reservoir Area of China. Here, we describe the first fecal microbiome diversity study of H5N1-infected migratory birds. By investigating the influence of H5N1 infection on fecal bacterial communities in infected and uninfected individuals, we found that H5N1 infection shaped the gut microbiota composition by a difference in the dominance of some genera, such as Aeromonas and Lactobacillus. We also found a decreased α diversity and increased β diversity in infectious individuals. Our results highlight that increases in changes in pathogen-containing gut communities occur when individuals become infected with H5N1. Our study may provide the first evidence that there are statistical association among H5N1 presence and fecal microbiota compositional shifts, and properties of the fecal microbiota may serve as the risk of gut-linked disease in migrates with H5N1 and further aggravate the disease transmission.